TAṬWĪR WASĪLAH AL-TAʿLĪM ʿALĀ ASAS ANDRŪWĪD - Rahmawati Ali (Jurnal Al-Maqoyis, 2020)
The objectives of this study are: to develop Android-based learning media for reading skills, to measure the validity of the media by giving questionnaires to experts and to students to find out student responses. The objectives of this study are: 1. to find out the steps for developing android-based learning media for android-based reading skills, 2. To find out student responses about android-based learning media that have been developed. This research is research and development. By adapting the development steps known as ADDIE (Analysis, Design, Development, Implementation and evaluation).  Researchers will develop an Android-based reading skill learning media which is then validated by several experts, such as Arabic language experts, material experts, media experts and Arabic language learning practitioners. And then research subjects are 8 students. The data collection techniques use: observation, interviews and questionnaires. The results of this study are: 1. Application of Android-based learning media to read Arabic for students of UPB UIN ANTASARI Banjarmasin, using steps known as ADDIE. 2. By using a range of 1-5 validation of learning media in terms of language with an average score of 4.5 (very good), validation of learning media in terms of material with an average score of 4.4, validation of learning media in terms of media with a score an average of 4.5 (very good) validation of learning media from learning practitioners with an average score of 4.4 (very good). With a student response with an average score of 4.4 (very good). So with the results of this study, it can be concluded that the Android-based learning media for learning reading skills is appropriate to be used as a medium for learning reading skills.